Senescence evasion in melanoma progression: uncoupling of DNA‐damage signaling from p53 activation and p21 expression. (14th January 2013) - MacKenzie Ross, Alastair D.; Cook, Martin G.; Chong, Heung; Hossain, Mehnaz; Pandha, Hardev S.; Bennett, Dorothy C.
Summary The best‐established function of the melanoma‐suppressor p16 is mediation of cell senescence, a permanent arrest following cell proliferation or certain stresses. The importance of p16 in melanoma suggests indolence of the other major senescence pathway through p53. Little or no p53 is expressed in senescent normal human melanocytes, but p16‐deficient melanocytes can undergo p53‐mediated senescence. As p16 expression occurs in nevi but falls with progression toward melanoma, we here investigated whether p53‐dependent senescence occurs at some stage and, if not, what defects were detectable in this pathway, using immunohistochemistry. Phosphorylated checkpoint kinase 2 (CHEK2) can mediate DNA‐damage signaling, and under some conditions senescence, by phosphorylating and activating p53. Remarkably, we detected no prevalent p53‐mediated senescence in any of six classes of lesions. Two separate defects in p53 signaling appeared common: in nevi, lack of p53 phosphorylation by activated CHEK2, and in melanomas, defective p21 upregulation by p53 even when phosphorylated.